Caribbean scleractinian corals exhibit highly variable tolerances to acute hypoxia - Pontes, Emma; Langdon, Chris; Al-Horani, Fuad A. (Frontiers in Marine Science, 2023)
Introduction Climate change, and the increase in sea surface temperature, is exacerbating ocean deoxygenation because of the inherent property of seawater to sequester less dissolved gas, such as oxygen, at warmer temperatures. While most coral reef studies focus on the effects of thermal stress and ocean acidification, few studies acknowledge the threat of hypoxia. Hypoxia is traditionally defined as 6.3 kPa (2 mg L-1 O2), however, a universal hypoxia threshold is not useful given the vast range of responses among marine organisms. The range of metabolic responses and tolerances to hypoxia are unknown for Caribbean coral species and their algal symbionts. Objective Here, we quantified the spectrum of acute hypoxia tolerances and the range of metabolic responses of six ecologically and structurally important Caribbean coral species (Acropora cervicornis, Siderastrea radians, Siderastrea siderea, Porites astreoides, Porites porites, and Orbicella faveolata) and their algal symbionts (Symbiodinium, Breviolum, and Durusdinium spp.). Methods A total of 24 coral fragments (4 individuals per species) were exposed to 10 distinct oxygen concentrations ranging from normoxia (20.38 kPa) to severe hypoxia (3.3 kPa). We used intermittent flow respirometry to measure coral host respiration in the dark and algal symbiont photosynthesis in the light at each oxygen level. We determined a line of best fit for the metabolic rate vs. PO2 data and calculated the critical oxygen partial pressure (PO2 crit), a method that has not been tested on symbiotic species. Results Coral species and their algal symbionts measured here displayed a wide range of hypoxia tolerances. For the coral hosts, PO2 crit values differed roughly two-fold ranging from 5.74 kPa to 16.93 kPa, and for the algal symbionts, PO2 crit values differed roughly three-fold ranging from 3.9 kPa to 11.3 kPa. Discussion These results should be regarded as a first step to characterizing the metabolic response and acute tolerance of multiple coral hosts and algal symbionts to a wide range of oxygen concentrations. Given that some PO2 crit values were above the generally accepted hypoxia threshold, these results have implications for the community composition of reefs under a rapidly changing climate and can guide purposeful reef restoration.